KAJIAN FILOSOFI TARI BARIS PUTUS PADA UPACARA PITRA YAJÑA DI DESA SINABUN KECAMATAN SAWAN KABUPATEN BULELENG (Vidya Darsan: Jurnal Mahasiswa Filsafat Hindu, 2025)
The performance of the Baris Putus Dance as a sacred dance acts as an accompaniment to thePitra Yajña ceremony in Sinabun Village. To increase the sacredness of the performance,philosophical studies are an important foundation for the sustainability and also increase thesacredness of the Baris Putus Dance in its performance at the Pitra Yajña ceremony. Based onthis background, in this study there are three problems that will be discussed, including; (1)What is the basis for the sustainability of the Baris Putus Dance at the Pitra Yajña ceremonyin Sinabun Village, (2) What is the form and function of the Baris Putus Dance at the PitraYajña ceremony in Sinabun Village, (3) What is the philosophical meaning contained in theBaris Putus Dance at the Pitra Yajña ceremony in Sinabun Village. The theories used inanalyzing the formulation of the problem are (1) Koentjaraningrat's religious theory, (2)Talcott Parsons' Structural Functional Theory, (3) Pierce's Semiotic Theory. The methods usedto collect data are: observation, interviews, documentation and literature studies. Thecollected data were analyzed using qualitative descriptive analysis methods with steps of datareduction, data presentation, and drawing conclusions. The results of the research and dataanalysis show that: (1) The basis for the sustainability of the Baris Putus Dance in the PitraYajña ceremony is seen from the perspective of the Pitra Yajña ceremony, the role of religionand religious awareness, and the role of the community and the Village Government. (2) Theform and function of the Baris Putus Dance seen from its form consists of movement andchoreography, costumes, and the performance process. then the performance function consistsof religious functions, social functions, and preservation functions. (3) The philosophicalmeaning of the Baris Putus Dance in the Pitra Yajña ceremony, seen from the meaning of thecostume, harmony, and karmapala.
Keywords: philosophical study, baris putus dance, pitra yajña ceremony